UPM's MM Programme among the best. - New Straits Times, Hussin Rahman (2003)
Universiti Putra Malaysia's Graduate School og Management (GSM) has had state-of-the-art- wquipment installed and its facilities refurbished, and is now training professionals for the corporate world and industry.